KEBIJAKAN PEMERINTAH BAGI PELINDUNGAN DAN KESELAMATAN MASYARAKAT DARI PENULARAN COVID 19 DI INDONESIA - Rosmeri Elsye (Fakultas Politik Pemerintahan IPDN, 2021)
Abstract This paper aims to get a clear picture to some extent, the Government's policy for the protection and safety of the public from the transmission of covid 19, because the transmission rate until February 2021, confirmed above 1.3 million positive people who were infected, and died above 30,000. more residents of the Community. While those who recovered were confirmed as many as 900 people. As a result of the increasing number of positive confirmations, it has an impact on the availability of isolation rooms, for the infected community, the availability of these spaces is approaching the allowable threshold according to WHO standards, the number of people who died, due to covid 19, burial grounds are needed, while the land is currently very limited, so it is necessary to add land and a new location for the burial place. This paper uses a qualitative descriptive method, and the data sources are obtained from print media, electronic media, and literature books and other documents related to the handling of covid 19. In conclusion, the government has made various efforts, including recofusing and relocating the APBN budget and APBD based on Perpu 1 of 2020, concerning State Financial Policy and Stability of the State Financial System, related to the handling of Covid 19 in Indonesia, this policy was adopted so that in overcoming and providing assistance to affected communities, as well as assistance to MSMEs and providing tax incentives, especially Article Income Tax 21 for affected entrepreneurs, and some other assistance such as providing basic necessities to affected communities, assistance to communities whose salaries are below 5 million per month, has a clear legal basis in its implementation. This program by the Government will be continued in 2021, until COVID-19 has subsided and is no longer there. The main priority programs for the 2021 fiscal year are Public Health and National Economic Recovery. The Coordinating Minister for the Economy, Mr. Airlangga Hartarto, stressed. Keywords: Policy, Protection, Community Safety, Covid Pandemic 19.